Project based learning approach for undergraduate mechatronics education using the Arduino online platform - Simona Domazetovska; Jovana Jovanova; Viktor Gavriloski (Military Academy ''General Mihailo Apostolski'', 2019)
The main objective of this paper is to present an innovative approach in project-based learning for an elective course: Fundamentals of mechatronics systems. The course is designed for 3rd year mechanical engineering students from various study programs. Implementing a project-based syllabus of an undergraduate course in mechatronics is a challenging task as it combines knowledge from mechanical engineering, computer science, electronics and control systems. The project based learning is presented through student projects inspired by the kinetic sculptures, which combines the mechatronics with the creative side of the art. By creating a project based on kinetic sculptures, the students were assigned to design and create moving smart structures with integrated microcontrollers using the Arduino online platform. Arduino is an inexpensive, straightforward and surprisingly powerful platform for implementation of algorithms in order to create real projects. The purpose of this paper is to present a successful methodology for teaching mechatronics by developing goal-oriented student projects based on open source platform within this course in the Faculty of Mechanical Engineering in Skopje. The structure, organization and evaluation of the course are explained, while the results indicate that our course structure provides an effective means for learning mechatronics.